Corrective Feedback In Eap Speaking Class - Dewi Wardah Mazidatur Rohmah; Abdul Halim (Journal on Education, 2023)
Research on Oral Corrective Feedback, especially related to its factors, has become a topic that is still widely discussed in teaching English because various application contexts will produce different conclusions. That is why it is important to study this topic further where this research aims to test a group by applying a single pretest-posttest method by providing oral Corrective Feedback. The participants in this study were a lecturer and 27 students in a Speaking English for Academic Purposes (ESP) class at the State Islamic University in Malang, East Java. The results showed an increase in the mean score from the pretest to the posttest. This means that giving Corrective Feedback provides benefits during the learning process for students in improving. Several factors in Corrective Feedback can explain how students respond to the Corrective Feedback given so that Corrective Feedback can play a significant role in improving the competence of speaking English. It is hoped that by understanding the use of Corrective Feedback, teachers, lecturers and educational practitioners will better understand which types of Corrective Feedback can have a positive impact on improving English speaking competence for English learners as a foreign language.